An Evaluation Of Pakistan's Food Supply And Security - Muhammad Osama Munir; Muhammad Ali Hussain; Tanees Yaseen; Maria Bibi; Kalsoom Kalsoom; Ayesha Ayesha; Afsheen Afsheen; Aneesa Khursheed; Haneen Fazal; Sadia Shafqat; Tehreem Tehreem (Utan Kayu Publishing, 2025)
Food insecurity remains a pressing issue globally, impacting over a billion individuals, with governments striving to address this challenge as a priority. Regions such as Asia and the Pacific Islands exhibit the highest levels of food insecurity, while Sub-Saharan Africa, although severely affected, shows slightly lower rates. Among the countries grappling with this crisis, Pakistan stands out as one of the most severely affected. A growing number of its population is chronically food insecure, which exacerbates the nation's ongoing food crisis. Recent developments in global methodologies and the availability of more precise data have allowed for better monitoring and analysis of food security trends worldwide. Key indicators, such as population statistics, food balance sheets, and consumption patterns, have become crucial tools in understanding the depth of the issue. In the case of Pakistan, these improved tools have revealed that the Prevalence of Undernourishment (PoU) for the period 2017-2019 reached 12.3%, marking a slight increase from the previous figure of 12.0% recorded the year before. This increase in the PoU reflects the country's ongoing struggle to meet Sustainable Development Goal (SDG) indicator 2.1.1, which seeks to eradicate hunger and ensure access to safe and nutritious food for all. Despite the country's efforts to address this issue, the number of people unable to meet their basic calorie needs continues to rise, with an estimated 26 million individuals currently facing chronic hunger. As the food crisis in Pakistan persists, it underscores the need for more effective strategies and interventions to combat food insecurity and ensure that the basic nutritional requirements of its population are met.